Small-scale variability in benthic habitat shapes size structure differences in the sea urchin Echinometra lucunter - Rodríguez-Barreras, Ruber (2026)
Introduction: Coral reefs have undergone widespread degradation, reducing ecosystem structural complexity and altering benthic habitat conditions. These changes can affect herbivorous invertebrates such as the sea urchin Echinometra lucunter, a key herbivore and bioeroder that can function as a bioindicator of environmental quality. Objectives: This study evaluated whether reef condition influences the population structure of E. lucunter by comparing benthic composition, rugosity, density, and test diameter between a healthy and a degraded zone at Isla de Cabra, Puerto Rico. Methods: Two reef zones at Isla de Cabra were sampled. Benthic cover was quantified using photo quadrats analyzed with CPCe software. Rugosity was calculated using the chain-and-tape method, and urchin density and test diameter were obtained from replicated quadrats and morphometric measurements. Results: The healthy zone showed higher coral and turf algae cover and greater rugosity, whereas the degraded zone was dominated by macroalgae. Although E. lucunter density did not differ significantly between zones, individuals from the healthy zone were significantly larger (4.3 ± 0.8 cm) than those from the degraded zone (3.5 ± 0.9 cm). The degraded zone exhibited a size distribution skewed toward smaller classes, suggesting growth limitation under lower habitat quality conditions. Conclusions: Local variability in benthic habitat structure influences the size structure of E. lucunter, while population density remains relatively stable. Size-based metrics reflect small-scale habitat differences and complement traditional benthic descriptors when assessing local habitat condition in shallow Caribbean reefs.